Dynamic behavior of reinforced concrete frame structure during construction - Tian, Ming-ge; Yi, Wei-jian (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2008)
The effects of concrete’s time-variant elastic modulus, casting structural components, assembling temporary shoring framework system, and shock by operating construction equipment on dynamic behavior of the reinforced concrete frame structure during construction were investigated. The dynamic tests of an eight-storey reinforced concrete frame structure during full-scaled stages of the sixth storey construction cycle were carried out by ambient vibration. Natural frequencies, corresponding mode shapes and damping ratio were determined by power spectrum processing the tested signal data in frequency domain. The changes of frequencies, mode shapes and damping ratios at different construction stages were given. The results show that natural frequencies and modal damping ratios reach the maximum at stage of casting fresh concrete, especially for higher modes. Modal damping ratios at each construction stage are less than 5% of those during usage.